The Influence of Service Quality, Customer Trust and Word of Mouth on Customer Loyalty at Ana Motor Badung Workshop - Rismayani, Ni Putu Sri Rahayu; Suardhika, I Nengah; Rihayana, I Gede (Journal of International Conference Proceedings, 2023)
Given the increasingly fierce level of competition and also the things that need to be strengthened so that customers remain loyal to using workshop services, therefore, it is important to conduct further studies that need to be considered by the Ana Motor workshop regarding how efforts should be made to increase customer loyalty in using workshop services. As a result, the purpose of this research is to investigate the impact of service quality, customer trust, and word of mouth on customer loyalty at the Ana Motor Workshop. This research was conducted in Badung Regency which is located at the Ana Motor Badung workshop. The method of collecting data through distributing questionnaires to 96 respondents for customers who have used repair services at the Ana Motor workshop at least 3 times. The sampling defined by Cochran was employed in this study, and the sampling method used was purposive sampling. For this study, multiple linear analysis techniques are used, which are conducted using the SPSS 25. 0 application for Windows. The results of the analysis show that service quality, customer trust, and word of mouth has a positive and significant effect on customer loyalty at the Ana Motor Badung workshop.